Raw post experiment preference data - Judt, David M.; Lawson, Craig P.; Lockett, Helen (Cranfield University, 2017)
Raw data of participant responses to ranking the position preference order.
Keywords: Aircraft assembly'; 'Wing leading edge'; 'Position preference'; 'Wing systems'; 'Aerospace Engineering'